Addressing the dichotomy between individual and societal approaches to personalised medicine in oncology. (June 2019) - Salgado, Roberto; Solit, David B.; Rimm, David L.; Bogaerts, Jan; Canetta, Renzo; Lively, Tracy; Lyerly, Kim; Span, Paul N.; Bateman-House, Alison; Makady, Amr; Bergmann, L.; Nagai, Sumimasa; et al.
Abstract: Academic, industry, regulatory leaders and patient advocates in cancer clinical research met in November 2018 at the Innovation and Biomarkers in Cancer Drug Development meeting in Brussels to address the existing dichotomy between increasing calls for personalised oncology approaches based on individual molecular profiles and the need to make resource and regulatory decisions at the societal level in differing health-care delivery systems around the globe. Novel clinical trial designs, the utility and limitations of real-world evidence (RWE) and emerging technologies for profiling patient tumours and tumour-derived DNA in plasma were discussed. While randomised clinical trials remain the gold standard approach to defining clinical utility of local and systemic therapeutic interventions, the broader adoption of comprehensive tumour profiling and novel trial designs coupled with RWE may allow patient and physician autonomy to be appropriately balanced with broader assessments of safety and overall societal benefit. Highlights: Develop biomarkers using rigorous methodology, rationality in clinical context, not limited to drug development. Standardise biomarker testing seeking equivalence between Companion Diagnostics and Laboratory-Developed Tests. Improve clinical study designs to include patient-centred end-points and core outcome sets. Bridge the gap between individualised and population-based oncology using real-world evidence.